Causes Inhibiting Proactive Behavior of University Staff: Focusing on the Impact of Contextual Factors in University Organizations - Yuya HORIKAWA (AAOS Transactions)
This study aims to explore the background behind the lack of proactive behavior among university staff from the perspective of contextual factors within university organizations. Through the analysis of interviews with 13 university staff members, it was revealed that the inhibiting factors for proactive behavior among university staff include the unique structure of university organizations, the nature of the organization that hinders change, impacts reflected in the field, and reasons for hesitating to engage in proactive behavior. This suggests that university staff are not as encouraged to take proactive behavior by their organizations as employees in private companies, and there are contextual factors that make it difficult for them to take action. Therefore, to increase proactive behavior among university staff in the future, it is crucial to ensure the legitimacy of changes in management and operations by creating legitimacy through higher-ups, considering the contextual factors of university organizations, rather than simply enhancing motivational mechanisms and encouraging action.